The effect of environmental tax and economic complexity on environmental sustainability in Latin America (1995-2020) - Gómez, Mario (Paradigma Económico, 2025)
This paper studies the influence of economic complexity, environmental tax, renewable energy, and foreign direct investment on environmental sustainability for selected Latin American countries from 1995 to 2020. Panel data analysis was used in the study. In addition, the moment quantile regression method was applied. The results demonstrate evidence of at least a cointegration relationship between the variables. The relationship between economic complexity and sustainability is U-shaped and is confirmed in the quantiles in the upper part of the distribution (0.6, 0.7, 0.8, and 0.9). The Load Capacity Curve (LCC) hypothesis is validated. Similarly, renewable energy and FDI have a positive relationship with sustainability and are confirmed in most distribution quantiles. The Pollution Halo hypothesis is validated: Foreign Direct Investment (FDI) helps reduce pollution. The environmental tax also has a positive relationship and is confirmed in the 0.9 quantile.